Installing Method and Subconscious Learning: A Sustainable English Learning Innovation Through Subconscious Knowledge Transfer in Kuanta Indonesia - Ah. Zakki Fuad; Suparto Suparto; Nina Indriani; Jauharoti Alfin; Muhammad Rey Dafa Ahmadi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to analyze the design, concept, and implementation of the Installing Method and Subconscious Learning in English learning at Kuanta Indonesia. The study also seeks to explore how subconscious-based learning can accelerate English mastery without traditional memorization and repetitive drills. Method: This research employed a descriptive qualitative approach conducted at Kuanta Indonesia as the research site. Data were collected through observations, interviews with master installers and learners, and documentation analysis. The data analysis process involved unitizing, recording, reducing, inferring, analyzing, and narrating to ensure data trustworthiness and comprehensive interpretation. Results: The findings reveal that the Installing Method emphasizes subconscious activation through alpha-wave learning conditions, allowing learners to absorb knowledge naturally and automatically. The learning process minimizes conscious memorization and analytical thinking, resulting in relaxed and efficient learning experiences. Students demonstrated rapid English mastery, improved confidence, and positive behavioral changes. The implementation includes structured learning programs, subconscious-based knowledge transfer, and rule-based learning environments that support automatic language acquisition. Novelty: This study introduces a new paradigm in English learning through subconscious installation rather than conventional learning methods. The Installing Method integrates subconscious brain activation, energy-based knowledge transfer, and behavioral transformation into a unified learning framework. This approach offers an innovative alternative for fast and effective English mastery and contributes to the development of transformative language learning methodologies.